Oxytocin levels in saliva correlate better than plasma levels with concentrations in the cerebrospinal fluid of patients in neurocritical care. (17th May 2018) - Martin, J.; Kagerbauer, S. M.; Gempt, J.; Podtschaske, A.; Hapfelmeier, A.; Schneider, G.
Abstract : In the converging fields of neuroendocrinology and behavioural neuroscience, the interaction between peripheral secretion and the central release of oxytocin in humans has not yet been comprehensively assessed. Because the human brain is not directly accessible and the collection of human cerebrospinal fluid (CSF) usually requires invasive procedures, easier accessible compartments such as blood or saliva have attracted increasing attention. In the present study, we prospectively determined oxytocin concentrations in the 3 compartments comprising the plasma, CSF and saliva of 50 critically ill patients with neurological and neurosurgical diseases. All samples per patient were collected concomitantly. Oxytocin was measured by a highly sensitive and specific radioimmunoassay. The strength of correlation was assessed by the Spearman rank correlation coefficient. Correlation analyses revealed modest to strong correlations for oxytocin between the saliva and CSF compartments, whereas predominantly weak correlations were found between the CSF and plasma, as well as between the plasma and saliva compartments. In conclusion, we have demonstrated modest to strong correlations between the saliva and CSF compartments suggesting that saliva oxytocin may help to assess CSF oxytocin levels. By contrast, plasma oxytocin failed to correspond well with CSF oxytocin levels because predominantly weak correlations were found between the CSF and plasma, as well as between the plasma and saliva compartments, which are unlikely to have any biological relevance. Further research is needed to clarify to what extent saliva oxytocin may serve as a biomarker reflecting brain oxytocin activity.